The effect of playing formation on high-intensity running and technical profiles in English FA Premier League soccer matches - Bradley, P. S.; Carling, C.; Archer, D.; Roberts, J.; Dodds, A.; Di Mascio, M.; Paul, D.; Gomez Diaz, A.; Peart, D.; Krustrup, P. (Journal of Sports Sciences, 2011)
The aim of this study was to examine the effect of playing formation on high-intensity running and technical performance during elite soccer matches. Twenty English FA Premier League games were analysed using a multiple-camera computerized tracking system (n = 153 players). Overall ball possession did not differ (P > 0.05) between 4-4-2, 4-3-3 and 4-5-1 formations (50%, s = 7 vs. 49%, s = 8 vs. 44%, s = 6). No differences were observed in high-intensity running between 4-4-2, 4-3-3 and 4-5-1 formations. Compared with 4-4-2 and 4-3-3 formations, players in a 4-5-1 formation performed less very high-intensity running when their team was in possession (312 m, s = 196 vs. 433 m, s = 261 vs. 410 m, s = 270; P < 0.05) but more when their team was not in possession (547 m, s = 217 vs. 461 m, s = 156 vs. 459 m, s = 169; P < 0.05). Attackers in a 4-3-3 performed 30% more (P < 0.05) high-intensity running than attackers in 4-4-2 and 4-5-1 formations. However, the fraction of successful passes was highest in a 4-4-2 (P < 0.05) compared with 4-3-3 and 4-5-1 formations. The results suggest that playing formation does not influence the overall activity profiles of players, except for attackers, but impacts on very high-intensity running activity with and without ball possession and some technical elements of performance.